PERLINDUNGAN KONSUMEN YANG MENGALAMI KERUGIAN AKIBAT KELALAIAN PELAKU USAHA (Studi Kasus Putusan Perkara Nomor: 474/Pdt.G/2011/PN.JKT.PST) - Bambang H.R Gultom, - (2019)
This study aims to find out about whether Consumer Protection against lossessuffered by consumers due to negligence of business actors and forms of compensation as a result of negligence of business actors according to CaseDecision Number: 474 / Pdt.G / 2011 / PN.JKT.PST regarding cases Unlawfully carried out by Khayangan Restaurant in Nikko HotelInternational. This study is a normative juridical study, the research approach used uses a legal approach and cases while the sources of legal material used include primary legal materials, secondary legal materials and tertiary legal materials. The legal material collection procedure used islibrary research. Based on the results of the research and discussionresulting in the first conclusion, Law Number 8 of 1999 concerning Consumer Protection (UUPK) has provided protection to consumers frombusiness actors. Business actors must fulfill the rights of consumers. If there is a violation of consumer rights by the business actor, the UUPK hasprovided a dispute settlement institution between business actors andconsumers, namely non-litigation lines and general court lines.